2016
DOI: 10.15835/nsb849851
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals for the Serum Biochemistry and Lipid Profile of Male Broodstock African Catfish (<i>Clarias gariepinus</i>: Burchell, 1822) at Varied Ages

Abstract: The study established reference intervals and age variations in the serum biochemistry and lipid profile of cultured male broodstock African catfish. The evaluations were carried out on twenty (Clarias gariepinus biochemistry and lipid profile determinations. The overall mean ± SD values for the serum biochemistry parameters and lipid profile were as f phosphatase 12.42 ± 2.56 U/L; total proteins 3.70 ± 1.49 g/dl; albumin 1.60 ± 0.30 g/dl; globulin 2.10 ± 1.38 g/dl; albumin/globulin 1.53 ± 1.71; tot 0.52 mg/dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…(2015) ( Sparidentex hasta ), Okoye et al . (2016) ( Clarias gariepinus ), Shahsavani et al . (2010) ( Acipenser stellatus ), Srivastava & Choudhary (2011) ( Heteropneustes fossilis ), Tavares‐Dias & Moraes (2007) ( Ictalurus punctatus ), Tripathi et al .…”
Section: Introductionmentioning
confidence: 99%
“…(2015) ( Sparidentex hasta ), Okoye et al . (2016) ( Clarias gariepinus ), Shahsavani et al . (2010) ( Acipenser stellatus ), Srivastava & Choudhary (2011) ( Heteropneustes fossilis ), Tavares‐Dias & Moraes (2007) ( Ictalurus punctatus ), Tripathi et al .…”
Section: Introductionmentioning
confidence: 99%
“…This physiological characteristic may explain the higher serum levels of total proteins, urea, glucose, triglycerides and AST found in younger L. alexandri . However, Okoye et al (2016) found lower levels of ALT, AST, total proteins, cholesterol and triglycerides for older Clarias gariepinus . Nutritional and environmental differences can also have a strong influence on serum biochemistry in fish (Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 98%